An updated review on the potential antineoplastic actions of oleuropein. (22nd November 2021) - Zheng, Yudong; Liu, Zhenzhen; Yang, Xiulan; Liu, Lian; Ahn, Kwang Seok
Abstract : Oleuropein is an ester of elenolic acid and hydroxytyrosol (3, 4‐dihydroxyphenylethanol). It is a phenolic compound and the most luxuriant in olives. The detailed information related to the anticancer effects of oleuropein was collected from the internet database PubMed/Medline, ResearchGate, Web of Science, Wiley Online Library, and Cnki using appropriate keywords until the end of October 2021. Oleuropein has been shown to have antioxidant, anticancer, antiinflammatory, cardioprotective, neuroprotective, and hepatoprotective effects. Previous studies also revealed that oleuropein could effectively inhibit the malignant progression of esophageal cancer, gastric cancer, breast cancer, lung cancer, liver cancer, pancreatic cancer, ovarian cancer, prostate cancer, and cervical cancer. Recently, the role of oleuropein in inhibiting tumor cell proliferation, invasion, and migration and inducing tumor cell apoptosis has gained extensive attention. In this review, we have summarized the latest research progress related to the antioncogenic mechanisms and the potential role of oleuropein in targeting different human malignancies. Based on these findings, it can be concluded that oleuropein can function as a promising chemopreventive and chemotherapeutic agent against cancer, but its more detailed anticancer effects and underlying mechanisms need to be further validated in future preclinical as well as clinical studies.